Uso do EPANET para determinar pressões de serviço da rede de abastecimento de água de Lucas do Rio Verde - MT - Beregula, Renato Leandro (2018)
Trustful information about hydraulic behavior, especially of flows and pressures, from a water supply are essential to help when decisions are made and to accomplish an effective management. However, due the obstacle to measure the oscillations from this greatness along the day, the information related to them are, oftentimes, scarce and inaccurate. The lack of physical data obstructs the achievement of trustful hydraulic simulation, once trustful input data are necessary to have good answers of the model. To obtain a representative hydraulic model there is a chain of processes that must be followed which starts from the choice of a closed system up until data collection to validation of the model, being that some processes demand financial resources and time, for instance, the case of acquisition of equipment to collect the pressure, thereby many existents models do not represent the reality. To avoid mistakes, it was applied all of necessary steps in a closed system to obtain a model closer to the reality, creating an algorithm with a calibration capable to determinate which are the consumptions in the supply network in every hour of the day, providing so data to arrange more trustworthy hydraulic simulation, to the study area was elaborated a database georeferencing the data with the water system supply elements, using ArcGIS Software. Furthermore, it was developed low cost pressure measures, employed in the data collection in 15 points in the city during 43 days, and in the same period it was monitored the pressure in 16 units of pumping. Georeferienced database was used as basis to the construction of the hydraulic model in the EPANET Software, where it was arranged the hydraulic system. 383.904 pressure data were collected in 31 points, of which 66,7% were used to calibrate the model, and 33,3% to validate the efficiency. The calibration revealed itself efficient and the hydraulic simulation generates similar pressure results related to those observed in the network in covering all sites of collection.